Comparison of The Greulich-Pyle And Tanner-Whitehouse Methods for The Detection of Bone Age - Kaplan, Atilla; Yılmaz, Hakan (The Bulletin of Legal Medicine, 2020)
Aim: The aim of this study is to compare the most commonly used Greulich-Pyle atlas and Tanner-Whitehouse methods in the evaluation of left wrist radiography for bone age determination due to its medical and forensic importance in pediatric period. Materials and Methods: For this study, 150 girls between 11-16 years of age and 210 boys between 11-18 years of age are chosen. A total of 360 cases are separated into 12 groups according to their sex and age. The left wrist radiographs of the cases are evaluated retrospectively. The bone age in these cases are determined with the GP atlas, the TW2 and TW3 methods. RUS scores that are mostly applied in TW methods are used. The relation between methods and chronological age, difference and usability are researched. Results: In general, TW2 overestimated and TW3 underestimated the ages. In GP method, the differences between chronological age and bone age are not significant whereas in TW3 method the differences are significant. Conclusion: According to the results, the GP atlas was the more applicable method for the age groups included in this study.